1970
DOI: 10.1002/art.1780130608
|View full text |Cite
|
Sign up to set email alerts
|

Role of igg and igm antinuclear antibodies in formation of lupus erythematosus cells and extracellular material

Abstract: IgM and IgG antinuclear antibodies (ANA) have been compared for their ability to produce hematoxylin bodies (ECM) and LE cells. At equivalent ANA concentrations (determined by immunofluorescent staining of rabbit liver nuclei), IgM formed ECM indistinguishable from those produced by IgG but, even at very high concentrations, failed to produce LE cells. Inability of IgM ANA to produce LE cells is probably due to lack of complement fixation rather than to a difference in antinuclear specificity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

1971
1971
1995
1995

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…Nearly all of these sera contained sNP and N-DNA antibody simultaneously (18/21 or 86%), confirming the high degree of association previously found by precipitin analysis (10). Aside from being a very sensitive technique, this radioimmunoassay may be a more reliable diagnostic tool than the LE cell test since it has been reported that antinuclear antibody of the IgM class do not produce the LE cell phenomenon (23). It is of interest that only a very low degree of significant binding was observed with only 2 of 46 sera from patients taking hydralazine, a drug often associated with the induction of a lupuslike syndrome (24,25).…”
supporting
confidence: 78%
“…Nearly all of these sera contained sNP and N-DNA antibody simultaneously (18/21 or 86%), confirming the high degree of association previously found by precipitin analysis (10). Aside from being a very sensitive technique, this radioimmunoassay may be a more reliable diagnostic tool than the LE cell test since it has been reported that antinuclear antibody of the IgM class do not produce the LE cell phenomenon (23). It is of interest that only a very low degree of significant binding was observed with only 2 of 46 sera from patients taking hydralazine, a drug often associated with the induction of a lupuslike syndrome (24,25).…”
supporting
confidence: 78%
“…Aho, Harboe, and Leikola (20) found that the agglutination by RF of sheep cells coated with small amounts of IgG could be inhibited (36). Human Igl\I antinuclear antibodies in our experience also appear to be deficient in their ability to fix complemenit and to promote phagocytosis (37). Most of the previous work on inhibition of complement fixation by RF has employed inhibitioni of immune hemolysis as an indclicator so that no one has excluded the possibility that RF may fix complement at a position sufficiently distant from the cell surface so that, in spite of activation of the components, cell lysis may not occur.…”
Section: Discussionmentioning
confidence: 79%
“…Linear 5 to 30% sucrose gradients were prepared as outlined by Blondin and Mc-Duffie (13). Samples of serum or blister fluid (0.4 ml) sterilized by Millipore filtration and aged for 7 days at 25" to allow decay of complement activity were layered on gradients and centrifuged at 40,000 rpm (270,OOOg at the tip) for 16 hr at 4" in a SB 283 rotor in a B-60 International ultracentrifuge.'…”
mentioning
confidence: 99%